Extended chloramination significantly enriched intracellular antibiotic resistance genes in drinking water treatment plants. (1st April 2023) - Li, Haibei; Yu, Hongling; Liang, Yongbing; Zhang, Xudong; Yang, Dong; Wang, Lin; Shi, Danyang; Chen, Tianjiao; Zhou, Shuqing; Yin, Jing; Yang, Zhongwei; Li, Junwen; et al.
Highlights: Chloramination led to higher enrichment of iARGs than chlorination. iARG enrichment ceased if the duration of chloramination is shortened. Chlorination facilitated eARGs release than chloramination. The total iARG concentration increased with the increase of NH4 + –N concentration. Shortening chloramination duration help control iARG enrichment. Abstract: Chloramination and chlorination are both strong barriers that prevent the transmission of potential pathogens to humans through drinking water. However, the comparative effects of chloramination and chlorination on the occurrence of antibiotic resistance genes (ARGs) in drinking water treatment plants (DWTPs) remain unknown. Herein, the antibiotic resistome in water before and after chloramination or chlorination was analyzed through metagenomic sequencing and then verified through quantitative real-time polymerase chain reaction (qPCR). After the treatment of 90 min, chloramination led to higher enrichment of the total relative abundance of intracellular ARGs (iARGs) in water than chlorination, whereas chlorination facilitated the release of more extracellular ARGs (eARGs) than chloramination. According to redundancy and Pearson's analyses, the total concentration of the observed iARGs in the finished water exhibited a strong positive correlation with ammonium nitrogen (NH4 + –N) concentration, presenting a linear upward trend with an increase in the NH4 + –N concentration. This indicated that NH4 + –N is a crucial driving factor for iARG accumulation during chloramination. iARG enrichment ceases if the duration of chloramination is shortened to 40 min, suggesting that shortening the duration would be a better strategy for controlling iARG enrichment in drinking water. These findings emphasized the potential risk of antibiotic resistance after extended chloramination, shedding light on the control of transmission of antibiotic-resistant bacteria through water by optimizing disinfection procedures in DWTPs. Graphical abstract: Image, graphical abstract